Effect of Three Essential Oils and Their Combination on Mortality of Tribolium castaneum at Different Time Interval in Stored Wheat - Kumar , Ranjeet (Journal of Postharvest Technology, 2016)
The laboratory experiment was conducted to find out the actual time required by the essential oils to cause 100 percent mortality against Tribolium castaneum (Coleoptera: tenebrionidae). For this purpose three essential oils e.g. Murraya koenigii, Calistimone. citrinus and Citrus reticulata was selected and evaluated at 6,12,18 and 24 hr interval. 73.3 percent mortality was observed in grain treated with M. koenigii oil at 0.2 percent in 6 hr but it took 24 hours to kill all the insects. The oil of M. koenigii + C. citrinus at 0.1 percent each showed 56.7, 73.3, 93.3 and 100 percent mortality in 6, 12, 18 and 24 hours after treatment, respectively. A combination of M. koenigii + C. reticulata + C. citrinus oil at 0.07 percent each showed 56.7, 93.3, 96.7 and 100 percent mortality in 6, 12, 18 and 24 hours after treatment, respectively. The formulation containing M. koenigii + C. reticulata oil at 0.1 percent caused 50.0, 86.7, 96.7 and 100 percent mortality in 6, 12, 18 and 24 hours after treatment, respectively. The oil of C. reticulata oil and C. citrinus caused 30.0 and 23.3 percent mortality respectively.